1975
DOI: 10.1111/j.1432-1033.1975.tb20988.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the Distribution of Proteins Bound to CNBr‐Activated Sepharose 6B at the Electron‐Microscopic Level

Abstract: Proteins were covalently attached to Sepharose by the CNBr method. Their distribution across the carrier beads was studied at the electron microscopic level. The approach has been to ferritinstain and to section the gel beads. Ferritin was either coupled directly to the polysaccharide backbone of the carrier or conjugated with pure rabbit anti-aminopeptidase in order to visualize covalently bound leucine aminopeptidase by the immunferritin technique. The results corroborate earlier fluorescence microscopic fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Early efforts of protein imaging analysis used laborious microtome sectioning of the solid supports [60,61]. Layers thus prepared were then analyzed microscopically.…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 99%
“…Early efforts of protein imaging analysis used laborious microtome sectioning of the solid supports [60,61]. Layers thus prepared were then analyzed microscopically.…”
Section: Direct Visualization Of Protein Distribution In Solid-suppormentioning
confidence: 99%
“…Recent reports [5][6][7] have presented conflicting evidence concerning the distribution of immobilised ligands throughout the beaded agarose matrix. Therefore we cannot eliminate the explanation that a percentage of the immobilised ligand is substituted on the surface of the bead; the extent of this substitution having a direct bearing on the enzyme-ligand interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Recently the microscopic structure of these polysaccharide matrices has been investigated both with respect to their ability to withstand various activation procedures, in particular cyanogen bromide [4], and also the distribution of the immobilised ligand throughout the matrix following coupling [5,6], which in itself may be a function of the CNBr activation [7]. In a previous communication [4] we reported that beaded cross-linked dextrans were susceptible to structural damage during CNBr activation, whilst beaded agarose was not obviously affected provided that vigorous stirring was avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Substitution of these variables in equations ( 1 1)- (13) results in the following dimensionless equations:…”
Section: Model Formulationmentioning
confidence: 99%